Multivessel vs. Culprit Vessel-Only Percutaneous Coronary Intervention for ST-Segment Elevation Myocardial Infarction in Patients With Cardiogenic Shock: An Updated Systematic Review and Meta-Analysis - Xiong, Bingquan; Yang, Huiping; Yu, Wenlong; Zeng, Yunjie; Han, Yue; She, Qiang (Frontiers in Cardiovascular Medicine, 2022)
Background The optimal revascularization strategy in ST-segment elevation myocardial infarction (STEMI) patients complicating by cardiogenic shock (CS) remains controversial. This study aims to evaluate the clinical outcomes of multivessel percutaneous coronary intervention (MV-PCI) compared to culprit vessel-only PCI (CO-PCI) for the treatment, only in STEMI patients with CS. Methods A comprehensive literature search was conducted. Studies assessed the efficacy outcomes of short (in-hospital or 30 days)/long-term mortality, cardiac death, myocardial reinfarction, repeat revascularization, and safety outcomes of stroke, bleeding, acute renal failure with MV-PCI versus CO-PCI in STEMI patients with CS were included. The publication bias and sensitivity analysis were also performed. Results A total of 15 studies were included in this meta-analysis. There was no significant difference in short- and long-term mortality in patients treated with MV-PCI compared to CO-PCI (odds ratio [OR] = 1.17; 95% confidence interval [CI], 0.92–1.48; OR = 0.86; 95% CI, 0.58–1.28). Similarly, there were no significant differences in cardiac death (OR = 0.67; 95% CI, 0.44–1.00), myocardial reinfarction (OR = 1.24; 95% CI, 0.77–2.00), repeat revascularization (OR = 0.75; 95% CI, 0.40–1.42), bleeding (OR = 1.53; 95% CI, 0.53–4.43), or stroke (OR = 1.42; 95% CI, 0.90–2.23) between the two groups. There was a higher risk in acute renal failure (OR = 1.33; 95% CI, 1.04–1.69) in patients treated with MV-PCI when compared with CO-PCI. Conclusions This meta-analysis suggests that in STEMI patients complicating CS, there may be no significant benefit with MV-PCI compared with CO-PCI, and an increased risk of developing acute renal failure after MV-PCI intervention. Keywords: myocardial infarction, cardiogenic shock, percutaneous coronary intervention